THE IMPLEMENTATION OF ASSESSMENT IN CURRICULUM 2013 IN ENGLISH SUBJECT OF SMPN BULUKUMBA - Ray Suryadi (Journal of English Education, 2016)
The objectives of this research are (1) to find out the description of the implementation of the Assessment in Curriculum 2013 in English Subject of SMPN Bulukumba. (2) to identify the problems that the teachers face when implementing the assessment of Curriculum 2013. (3) to find out the solution of the problems. This research is done in several piloting schools in SMP Negeri Bulukumba. They are schools that are pointed by the government to implement the curriculum 2013. In addition, there was also one school which is not a piloting school to continue to implement the Curriculum of 2013. The participant of this research is the English teachers of the first grade. To collect the data the researcher used tape recorder and conducted interview with the teachers and headmaster as additional data. In analysing the data, the researcher used qualitative method. According to Patton (1987) that qualitative method enables the researcher to interview and to interprete the result according to the real-life situation on the site. It allows the use of expressing language and the presence of the participants’ voices in text. This is important because voices brings in other aspects such as moods and tones that may contribute to the quality of data. The findings of this research showed that (1) The respondents had conducted the assessment of curriculum 2013 well in accordance with the assessment implementation guides, eventhough in another side, they haven’t understood it as a whole, lack of material in the text book, and still need more training. (2) There were five numbers of problem were found from the teachers’ perception on the assessment in curriculum 2013, such as: (a) Teachers face problems dealing with the curriculum changing particularly in assessment process, (b) Teachers face problems dealing with the lack of material in the text book, (c) Teachers face problems dealing with the assessment integration of listening to speaking and reading to writing, (d) Teachers face problems dealing with student’s attitude assessment, (e) Teachers face problems dealing with time allocation. (3) The problems solution were suggested by the teachers and headmaster. The points in the suggestion was the teacher should be able to adapt with the curriculum 2013, so would have been easy to implement it well